Comparing the relationship between Turkey and the World Bank in the 1980s vis-à-vis the 1990s - Atabaş, Hacer. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2018., 2018)
The thesis discusses the conditions of disbursement and utilization of development assistance by comparing and contrasting the relationship between Turkey and the World Bank in the 1980s and the 1990s – the years in which the relationship took a diﬀerent course- and concludes that a development assistance project depends on the internal and external conditions of an aid recipient country; stability of the political environment in the country, the country’s eagerness to adopt the project, and the mutual strategic interests and interdependency of the country and the aid agency. Aid’s utilization is aﬀected by the political conditions of the aid recipient country (whether they allow the prioritization of the development agenda) and its disbursement is aﬀected by the political structure of aid agencies (whether they are under the influence of their home countries and major shareholders). In the context of the literature on development assistance, I conduct documentary analysis of the organization and research reports by independent researchers published by the World Bank, and in-depth interviews with the four former Undersecretaries of the Treasury Department of the Turkish republic who oﬃciated during the 1980s and 1980s, which lead to the conclusions.
Keywords: Turkey -- Economic conditions -- 1980-; Economic assistance -- Turkey.